Metastatic Urachal Carcinoma Treated With Several Different Combined Regimens: A Case Report - Zheng, Han; Song, Wei; Feng, Xiemin; Zhao, Hong (Frontiers in Oncology, 2021)
Urachal carcinoma is a rare bladder malignance. This study presents a case of an elderly patient with urachal carcinoma who was found to have pulmonary metastases 1 year after 5 recurrent resections. The patient was treated with up to 7 different chemotherapy regimens, including a VEGF monoclonal antibody and anti-PD-1 antibody. This is the first report of PD-1 antibody being used in patients with urachus, although the disease progressed after only four cycles of the application. The patient's disease was controlled by the FOLFIRI combined with the VEGF monoclonal antibody regimen. The most prominent issues at present are the difficulty of obtaining drugs for rare cancers and the lack of late-stage clinical trials to guide therapeutic decisions.